Experimental study of the efficiency of a solid-fuel pulsed plasma engine - Igibayev, Zh.B.; Khamzayev, A.K.; Yertayev, O.A.; Dosbolayev, M.K. (Recent Contributions to Physics, 2023)
The purpose of this work is to study the dependence of thrust-power characteristics and electrode geometry of a solid-fueled pulse-plasma engine (PPE) was carried out in a series of experiments. The results of the study revealed useful dependences that reveal the relationship between the capacitor capacity and the pulse bit of the PPE, as well as between the geometry of the electrodes and the thrust characteristics of the PPE. According to the obtained data the following conclusions can be made, with increasing the capacitor capacitance from 3μF to 5μF contributes to improving the traction characteristics, while reducing the distance between the electrodes by changing the anode diameter from 6mm to 10mm negatively affects the traction characteristics of a PPE. These dependencies were obtained by changing the voltage between the coaxial electrodes from 2kV to 3.5kV in 0.5kV increments. They play an important role in further improvement and optimization of the solid-propellant PPE design, as well as to ensure their effective operation in space conditions. The results obtained are valuable information for designers and engineers working in the field of space technology. They can be used in further research and development aimed at creating more efficient and reliable solid-propellant PPEs that can successfully perform the tasks of orbit correction and maintaining the stable position of small spacecraft. This opens new prospects for the development of space engineering and ensuring more efficient use of solid propellant in plasma engines.